Effects of different training intensities in high-intensity interval training (HIIT) on maximal aerobic velocity, hematological and muscle-damage markers in healthy young adults - Fatma Rhibi; Abderraouf Ben Abderrahman; Jacques Prioux; Cain C. T. Clark; Benoît Bideau; Sophia Besbes; Anthony C. Hackney; Urs Granacher; Hassane Zouhal (BMC, 2022)
Abstract This study aimed to examine the effects of two high-intensity interval training programs (HIIT) on maximal aerobic velocity (MAV), hematological variations and muscle damage markers in young healthy adults. Twenty-nine male physical education students, aged 20.3 ± 3.3 years, volunteered to participate in this study, and were randomly assigned to a control group (CG, n = 9) or two intervention groups (group 1 or 2). Intervention group 1 (n = 10) exercised at 100% of their MAV (EG100) while group 2 (n = 10) exercised at 110% MAV (EG110). Before and after the eight week training program, blood samples were drawn at rest, before, and after an intermittent exercise. Aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), C reactive protein (CRP), creatine kinase (CK) concentrations and hematological parameters (white blood cells [WBC], monocytes [MO], lymphocytes [LY], neutrophil [NE]) and lactate dehydrogenase (LDH) were measured. Post-hoc tests showed that MAV was significantly higher in EG110 compared to EG100 after HIIT (p < 0.01, ηp 2 = 0.05), whilst ALAT, ASAT, and CPR were significantly lower (p < 0.01; 0.02 < ηp 2 < 0.11) in EG110 compared to EG100. Moreover, post-hoc tests indicated that LY decreased significantly (p < 0.001, ηp 2 = 0.21) only for EG110. Furthermore, there were significant positive correlations for both EG100 and EG110 between MAV and ALAT (r = 0.66, p = 0.044 and r = 0.64, p = 0.041 respectively), CK (r = 0.67, p = 0.031 and r = 0.86, p = 0.030, respectively), LDH (r = 0.74, p = 0.014, and r = 0.071, p = 0.021, respectively). In addition, there was a significant positive correlation for both, EG100 and EG110 between MAV and LY (r = 0.79, p < 0.01; r = 0.72, p < 0.05, respectively). Concerning the relationship between MAV and NE, there was a significant positive correlation (r = 0.66; p < 0.05) only for EG110. Findings from this study revealed that HIIT at 110% MAV was more efficient to improve MAV and reduce muscle damage. In addition, we observed significant associations between performance improvements (MAV) and markers of muscle damage.